2012
DOI: 10.1021/jf3008376
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Hepatoprotective Effects of Polyphenol-Rich Extract from Houttuynia cordata Tea

Abstract: This study was designed to investigate the antioxidant activity, hepatoprotective effect, and phenolic composition of the ethyl acetate fraction (EAF) extracted from Houttuynia cordata tea. EAF was shown to exhibit strong ferric-reducing antioxidant power (FRAP) and scavenging activity against DPPH radical in vitro, and the antioxidant effects were further verified by suppressing CCl₄-induced oxidative stress in mouse liver at three tested doses of EAF (250, 500, and 1000 mg/kg bw). Pretreatment with EAF (1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 40 publications
6
63
0
Order By: Relevance
“…Our present study demonstrates that, among the six investigated species, the higher content of polyphenols, flavonols, and antioxidant properties in HC and MA plants may be the reason for their wide medicinal use. Both species can be used as potent medicinal herbs for novel bioactive compounds with high free radical scavenging activity, and extracts of these plants may been attractive alternative for managing oxidative stress-induced liver injury and drug-induced gastric ulcer [45,46]. Recently, Gargouri et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our present study demonstrates that, among the six investigated species, the higher content of polyphenols, flavonols, and antioxidant properties in HC and MA plants may be the reason for their wide medicinal use. Both species can be used as potent medicinal herbs for novel bioactive compounds with high free radical scavenging activity, and extracts of these plants may been attractive alternative for managing oxidative stress-induced liver injury and drug-induced gastric ulcer [45,46]. Recently, Gargouri et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study revealed that quercitrin markedly overturned NO production in RAW 264.7 cells and inhibited the progression of inflammation through down-regulation of the NF-κB pathway [36,37]. Furthermore, Tian et al [15] reported that an EA fraction derived from H. cordata was rich in the polyphenolic compounds quercitrin, quercetin, and hyperoside, which were responsible for the antioxidant and hepatoprotective merits of the tea. In agreement with these previous studies, our results indicate that the ability of HCE-EA to suppress production of inflammatory mediators might be attributable to its content of active components, in particular chlorogenic acid, hyperoside, and quercitrin.…”
Section: Discussionmentioning
confidence: 99%
“…(family Saururaceae) is a perennial food plant widely distributed throughout Southeastern Asia. This plant is a leaf vegetable that is used as a herbal tea, in salads, or cooked with other vegetables [15]. Also, It has been used in traditional medicine for treatment of suppuration, chronic bronchitis and pneumonia, otitis, and cystitis [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, it is the first time that the antiproliferative properties of the polyphenolic extract derived from selenium-enriched Ziyang tea against human breast cancer MCF-7 cells have been evaluated. [18,19], 50 g of dried tea leaves were thoroughly mixed with 500 mL of 80% ethanol, and were extracted three times at 70 C for 60 minutes for each extraction while being vigorously shaken. The obtained supernatant was further concentrated and precipitated by 1.0M ZnCl 2 (pH 6.2), and 0.4M hydrochloric acid was used to dissolve the sediments.…”
Section: Introductionmentioning
confidence: 99%